FAKTOR PENDUKUNG PRESTASI BOLABASKETPESERTA EKSTRAKURIKULER BOLABASKET DISMAN 1 DEPOK SLEMAN YOGYAKARTA - Fyea Mardiana dan Tri Ani Hastuti (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractBasketball sports achievements in SMAN 1 Depok local level has been good, yet at the national level has not beenencouraging, must be influenced by several factors. This study aims to determine the factors supporting extracurricularachievement in high school basketball N 1 Depok. This research is a descriptive study. The method used was asurvey, using data collected with a questionnaire. Subjects in this study were students who take extracurricularbasketball at SMAN 1 Depok, amounting to 25 students. Data analysis using descriptive percentages.The resultsshowed that the factors that support extracurricular achievement in high school basketball N 1 Depok by endogenousfactors of athletes indicator with a percentage of 89.00% in the category of very high physical and percentage of82.1% is categorized as very high. While exogenous factors of indicators a coach with a percentage of 87.95% iscategorized as very high, infrastructure 91.33% percentage categorized as very high, amounting to 86.53% thepercentage of organizations categorized as very high, by 88 percentage competition, 71% categorized as very high,and the percentage of 87.00% families categorized as very high. It can be concluded that the factors that supportthe achievement of extracurricular basketball SMAN 1 Depok by endogenous factors of 85.74% in the category ofvery high and amounted to 87.95 % of exogenous factors categorized as very high.Keywords: contributing factors, extracurricular basketball, SMAN 1 DepokAbstrakPrestasi olahraga bolabasket di SMA N 1 Depok ditingkat daerah sudah baik,namun di tingkat nasional belummenggembirakan, tentunya dipengaruhi oleh beberapa faktor. Penelitian ini bertujuan untuk mengetahui faktorpendukung pencapaian prestasi ektrakurikuler bolabasket SMA N 1 Depok. Jenis penelitian ini adalah penelitiandeskriptif. Metode yang digunakan adalah survei, dengan teknik pengumpulan data.(Instrumen) menggunakan angket.Subjek dalam penelitian ini adalah siswa (putra dan putri) yang mengikuti ekstrakurikuler bolabasket di SMA N 1Depok yang berjumlah 25 siswa. Analisis data menggunakan deskriptif persentase. Hasil penelitian menunjukkanbahwafaktor-faktor yang mendukung pencapaian prestasi ekstrakurikuler bolabasket SMA N 1 Depok berdasarkanfaktor endogen dariindikator atlet dengan persentase sebesar 89,00% masuk kategori sangat tinggi dan fisikpersentase sebesar 82,11% masuk kategori sangat tinggi. Sedangkan dari faktor eksogen dari indikator pelatih denganpersentase sebesar 87,95% masuk kategori sangat tinggi, sarana dan prasarana persentase sebesar 91,33% masukkategori sangat tinggi, organisasi persentase sebesar 86,53% masuk kategori sangat tinggi, kompetisi persentasesebesar 88,71% masuk kategori sangat tinggi, dan keluarga persentase sebesar 87,00% masuk kategori sangattinggi. Dengan demikian dapat disimpulkan bahwa faktor yang mendukung pencapaian prestasi ekstrakurikulerbolabasket SMA N 1 Depok berdasarkan faktor endogen sebesar 85,74% masuk kategori sangat tinggi dan faktoreksogen sebesar 87,95% masuk kategori sangat tinggi.Kata kunci: faktor pendukung, ekstrakurikuler bolabasket, SMAN 1 Depok